The Influence Of Entrepreneurship Leadership And Growth Mindset On Community Empowerment With Organizational Trust As An Intervening Variable: A Case Study Of Al-Ittifaq Islamic Boarding School, Ciwidey, Bandung - Mahdi, Uteng; Ranti, Benny; Rismadi, Bambang; Pakpahan, Marisi (Jurnal Pendidikan, Sains Sosial, dan Agama, 2024)
This study aims to analyze the Influence of Entrepreneurship Leadership and Growth Mindset on Community Empowerment with Organizational Trust as an Intervening Variable: A Case Study of Al-Ittifaq Islamic Boarding School, Ciwidey Bandung. This study uses a quantitative approach. The population of this study is the community in the Al-Ittifaq Islamic Boarding School environment, Ciwidey Bandung, who are members of an empowerment group managed by the Islamic boarding school, with a total of 300 farmer groups. The results of this study indicate that there is a positive influence Entrepreneurship Leadership towards Community Empowerment through Organizational Trust is proven because the path coefficient is 0.099 supported by a t count of 2.061 > 1.96 with a ρ-value of 0.040 < 0.05. In addition, there is an influence Growth Mindset towards Community Empowerment through Organizational Trust is proven because the path coefficient of 0.198 is supported by a t count of 2.729 > 1.96 with a ρ-value of 0.007 < 0.05. The conclusion of this study shows that the trust of the community in the Islamic boarding school environment towards the Leaders of the Boarding School and the organization of the Islamic boarding school, is able to mediate the influence of Entrepreneurship Leadership on Community Empowerment. This means that the entrepreneurial leadership style of the Boarding School Leaders will have a stronger influence on the empowerment program, if assisted by the high trust of the community in the Boarding School Leaders and the organization of the Islamic boarding school. The implications of this study can encourage the community in the Islamic boarding school environment to maintain their positive mindset , both towards the Islamic boarding school organization and the Boarding School Leaders, thereby increasing the trust and confidence of the community in the Boarding School Leaders and the Islamic boarding school and having an impact on the success of the empowerment program.